Hadith Criticism from the Perspective of Contemporary Islamic Education: Rereading the Hadith on a Wife’s Prostration to Her Husband in Muslim Family Culture - Rahmin Talib Husain; Hasyim Mahmud Wantu; Muh Arif; Selviyanti Kaawoan; Fitria N. Laiya; Syahrial Labaso; Rifa Tsamrotul Syaadah (Center for Research and Publication (PUSLITPEN), UIN Syarif Hidayatullah Jakarta, 2026)
This paper revisits the hadith of the wife prostrating herself to her husband in the light of Contemporary Islamic Education and Muslim family culture. This hadith is often cited in marriage sermons, family religious gatherings, and premarital guidance, but is often taken literally, which can reinforce unequal marital relations. This study uses qualitative library research, including takhrij al-hadith, i’tibar al-sanad, criticism of the sanad, criticism of the matan, and contextual analysis. The results indicate that the hadith reported by al-Tirmidhi is hasan li dhatihi: its chain is connected, most of its narrators are trustworthy, and the weakness of Muhammad ibn ‘Amr is supported by other routes. The Matan analysis shows that the wording is hypothetical and not a literal command to the wives to prostrate, but an affirmation that prostration is only for Allah. This study emphasizes the significance of hadith literacy as a basis for establishing a Muslim family on the principles of tawhid, mutual responsibility, mutual respect, and justice in the discourse and practice of Islamic education today.